Effect of SGLT2 inhibitors on left ventricular function in patients with acute myocardial infarction and left ventricular dysfunction: A single-center randomized study - Jijin Satheesh, Mugula Sudhakar Rao, Padmakumar Ramachandran, Jyothi Samanth (Journal of Applied Pharmaceutical Science, 2025)
Despite advances in medical therapy and improved access to percutaneous coronary intervention (PCI), the burden of heart failure after acute myocardial infarction (MI) remains high. We aimed to study the beneficial effects of sodium-glucose cotransporter 2 (SGLT2) inhibitors on left ventricular (LV) function in patients with MI and LV dysfunction (ejection fraction < 50%). We studied 72 diabetic patients (50 cases and 22 controls) who were admitted to our hospital with acute MI and underwent primary PCI. The case group received dapagliflozin as part of their diabetes management. Baseline echocardiographic parameters were recorded. The two groups were followed up for a median period of 5 months, with repeat echocardiography being performed at follow-up. Patients receiving dapagliflozin had a decrease in LV mass from pretreatment values of 222–190.8 g, which was statistically significant (p = 0.0003). Similar changes were reflected in the LV mass index, which reduced from 128.67 g/m2 at baseline to 110.9 g/m2 at follow-up (p = 0.0004). The LV ejection fraction by area length method increased from baseline means of 41.56%–45.02%. The control group’s mean LV mass did not show statistically significant change during follow-up. The ejection fraction measured by area length method improved from 44.1%, at baseline to 51.1% at follow-up. In patients with acute MI and LV dysfunction, SGLT2 inhibitors have improved LV remodeling by reducing LV mass and LV mass index with concomitant reductions in the interventricular septum, posterior wall, and relative wall thickness.
Keywords: SGLT2 inhibitors, acute myocardial infarction, heart failure, diabetes mellitus, systolic dysfunction, post-PCI